Simultaneous Determination of Multiple Active Components from Bushen Pills and Application in a Pharmacokinetic Study in Rats. (20th July 2020) - Li, Houli; Wang, Benjie; Yuan, Guiyan; Liu, Xiaoyan; Huang, Jing; Xiong, Lilong; Zhang, Di; Feng, Weiyi; Guo, Ruichen
Abstract : Bushen Pills (BSPs), as a traditional Chinese medicine (TCM), is widely used in clinic to enrich Yang, nourish Yin, stem essence, and strengthen kidneys. Two chromatographic methods, liquid chromatography-mass spectrometry (LC-MS) and liquid chromatography-tandem mass spectrometry (LC-MS/MS), were applied to analyze the multiple active components of BSPs in dosage form for quality evaluation and in rat plasma for pharmacokinetics study, respectively. Three active constituents of BSPs, including paeoniflorin (PF), berberine hydrochloride (BBR), and schizandrin (SCH), were simultaneously determined by the established LC-MS method with electrospray ionization (ESI) in positive selected ion monitoring (SIM) mode at m / z 503.1, 336.0, and 455.2. The contents of PF, BBR, and SCH were (6.112 ± 0.166) mg/g, (335.1 ± 14.95) μ g/g, and (5.867 ± 0.136) μ g/g in BSPs. On this basis, PF and BBR were selected as targeted analytes for the pharmacokinetic study of BSPs in rats. Memantine hydrochloride was used as an internal standard (IS), and the plasma samples were processed by liquid-liquid extraction with ethyl acetate. All the analytes were separated on a C18 reversed phase column, eluted with a mobile phase consisting of acetonitrile-formic acid (0.01%) (25 : 75, v /v ), and detected by ESI in the selected ion mode with multiple reaction monitoring (MRM). The target fragment ions were m/z 525.3 ⟶ 449.5 for PF, 336.2 ⟶ 320.2 for BBR, and 180.1 ⟶ 163.1 for IS. The linear ranges of PF and BBR were 5–500 ng/mL and 0.1–20 ng/mL with good linearity ( r 2  > 0.99). No obvious matrix effect was observed, and acceptable accuracy, precision, recovery, and stability were obtained. The proposed method has been successfully applied to the pharmacokinetic study of BSPs in rats after a single dose.